PENYUSUNAN KURIKULUM BLOK BAHASA INGGRIS VOKASIONAL - Yuanti, Erlin Estiana; Vardhani, Nabilla Kusuma (UI Scholars Hub, 2021)
This research aims at designing vocational block curriculum for Bachelor of Applied English Vocational College (BAE SV) UGM to assure the achievement of the study program’s competences based on the Independent Campus policy (MBKM) and to produce English Specialists in Public Relations as its graduate profile. The research employs qualitative method, using Research and Development approach in the three stages done, such as: (1) library study, (2) designing the block curriculum, and (3) validating the curriculum design by holding FGD with stakeholder users. The research produces a vocational English block curriculum based on CEFR Level C1 and SKKNI No.629/ 2016 on Public Relations (PR). There are four (4) blocks focusing on the skills of English for specific purposes in the first year, and four (4) blocks on the skills of English for public relation skills in the second year. In the third year, there is one (1) block of Interdisciplinary Skills, one (1) block of Research Skill and Academic English Writing skill. In the fourth year, there is one (1) block for Internship as a form of Independent Campus scheme and one (1) block for Final Project Writing as the requirement for graduation.